An innovative strategy to enhance the ensiling quality and methane production of excessively wilted wheat straw: Using acetic acid or hetero-fermentative lactic acid bacterial community as additives. (15th July 2022) - Yan, Jing; Sun, Yibo; Kang, Yuehua; Meng, Xingyao; Zhang, Huan; Cai, Yafan; Zhu, Wanbin; Yuan, Xufeng; Cui, Zongjun
Graphical abstract: Highlights: Ensiling EWS with acetic acid or heterofermentative LAB addition was first studied. Ensiling EWS with additives enhanced acetic acid fermentation. Ensiling EWS with additives preserved hemicellulose and cellulose content. Ensiling EWS with additives changed the homo-fermentation to hetero-fermentation. Ensiling EWS with additives improved the methane yield by 17.7–23.9%. Abstract: Ensiling is an effective storage strategy for agricultural biomass, especially for energy crops (mainly energy grasses and maize). However, the ensiling of excessively wilted crop straw is limited due to material characteristics, such as a high lignocellulosic content and low water-soluble carbohydrate and moisture contents. In this study, acetic acid or hetero-fermentative lactic acid bacterial community (hetero-fermentative LAB) were employed as silage additives to improve the ensiling process of excessively wilted wheat straw (EWS). The results showed that the additives inhibited the growth of Enterobacteriaceae and Clostridium_sensu_stricto_12, whose abundances decreased from 55.8% to 0.03–0.2%, respectively. The growth of Lactobacillus was accelerated, and the abundances increased from 1.3% to 80.1–98.4% during the ensiling process. Lactic acid fermentation was the dominant metabolic pathway in the no additive treatment. The additives increased acetic acid fermentation and preserved the hemicellulose and cellulose contents, increasing the methane yield by 17.7–23.9%. This study shows that ensiling with acetic acid or hetero-fermentative LAB is an effective preservation and storage strategy for efficient methane production from EWS.